2017
DOI: 10.1016/j.shaw.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Knee Loading and the Risk of Osteoarthritis of the Knee: A Systematic Review and a Dose-Response Meta-Analysis

Abstract: BackgroundOsteoarthritis of the knee is considered to be related to knee straining activities at work. The objective of this review is to assess the exposure dose-response relation between kneeling or squatting, lifting, and climbing stairs at work, and knee osteoarthritis.MethodsWe included cohort and case–control studies. For each study that reported enough data, we calculated the odds ratio (OR) per 5,000 hours of cumulative kneeling and per 100,000 kg of cumulative lifting. We pooled these incremental ORs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 41 publications
(92 reference statements)
5
77
0
4
Order By: Relevance
“…Yet there was no effect when squatting and kneeling were examined individually. This diversity in findings has been noted previously , and it highlights the need for attention to measurement, including whether compartmentalizing or differentiating among knee bending tasks accurately reflects real‐world work conditions in the frequency and duration of knee bending, and whether knee bending occurs in conjunction with lifting heavy loads . Some jurisdictions are trying to address these issues and have identified minimum thresholds for frequency and duration of kneeling related to work compensation claims , but in the absence of detailed evidence, thresholds are set high.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Yet there was no effect when squatting and kneeling were examined individually. This diversity in findings has been noted previously , and it highlights the need for attention to measurement, including whether compartmentalizing or differentiating among knee bending tasks accurately reflects real‐world work conditions in the frequency and duration of knee bending, and whether knee bending occurs in conjunction with lifting heavy loads . Some jurisdictions are trying to address these issues and have identified minimum thresholds for frequency and duration of kneeling related to work compensation claims , but in the absence of detailed evidence, thresholds are set high.…”
Section: Discussionmentioning
confidence: 63%
“…One domain of importance for education and intervention is the workplace. To date, numerous studies have examined the relationship of physically demanding occupations like farming, mining, and floor laying, as well as work activities like kneeling, squatting, and heavy lifting to the onset of OA .
A synthesis of 69 studies from 23 countries yielded strong and moderate evidence for lifting, cumulative physical loads, full‐body vibration, and kneeling/squatting/bending as increasing the risks of developing osteoarthritis (OA) in men and women. Strong and moderate evidence existed for no increased risk of OA related to sitting, standing and walking (hip and knee OA), lifting and carrying (knee OA), climbing ladders (knee OA), driving (knee OA), and highly repetitive tasks (hand OA). Greater attention is needed to improve measures assessing employment activities and recall periods. A lack of consistency in dose‐response information makes synthesizing data problematic and hinders practical recommendations.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOW workers perform such movements routinely during the installation of tracks and ballast 13 . Occupational ergonomic risk factors for osteoarthritis of the hip and knee have also become the focus of a recent WHO/ILO study initiative to assess the national and global burden of work‐related injuries 12,37 . Heavy rail construction vehicles require the use of foot pedals (such as for the throttle and brakes) to control the function of the vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, in a major review of the epidemiological evidence, National Institute for Occupational Safety and Health (NIOSH) concluded that a consistent relationship exists between MSDs and certain biomechanical risk factors, including heavy physical work, lifting and forceful movements, bending and twisting (nonneutral postures), static work postures, and WBV 8 . Since then, additional studies have shown that WBV is associated with neck disorders, 9,10 and repetitive kneeling in certain trades (ie, floor installer, roofer, and material handler) is causing occupational knee disorders 11,12 . In Germany, knee arthrosis in certain occupations was added in 2009 to the recognized list of occupational diseases no.…”
Section: Introductionmentioning
confidence: 99%